If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 6 + 2u Solving 8 = 6 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 8 + -2u = 6 + 2u + -2u Combine like terms: 2u + -2u = 0 8 + -2u = 6 + 0 8 + -2u = 6 Add '-8' to each side of the equation. 8 + -8 + -2u = 6 + -8 Combine like terms: 8 + -8 = 0 0 + -2u = 6 + -8 -2u = 6 + -8 Combine like terms: 6 + -8 = -2 -2u = -2 Divide each side by '-2'. u = 1 Simplifying u = 1
| 3x+2=x^2-25 | | X^2+9=14 | | 5x+4+x=-14 | | X^2-3=25 | | 7n^2-3=445 | | 13-s=8 | | 2/3(n-(5/6))=2.5 | | 5k^2-7=238 | | 6+4x+5x=51 | | 12/c=3 | | 6x+5+65=14x-10 | | 2+x-3x=2 | | 14(v+2)-2v=3(4v+1)-11 | | 2(f+4)=18 | | 2,7x0,5x4/5 | | 34=6x+3x+7 | | 9=2s+5 | | 3t^4=-t^2+2 | | 2(j-15)-1=3 | | pq+4opx+qy+z=0 | | 64=2x+7x+1 | | 6x+3-x=-22 | | 20x^2-32x+12=0 | | 114=6x+3x+6 | | 31.25=w/5 | | -9k=-10k+6 | | 4f=3+f | | v=4/3X3.14X10X2 | | -9s+8=-10s | | 4x-3x+7=12x-6-9 | | 1/6c=12 | | 4x+4=5x+6 |